Base‐Catalyzed Synthesis of Substituted Indazoles under Mild, Transition‐Metal‐Free Conditions1. Issue 29 (5th June 2013) - Thomé, Isabelle; Besson, Claire; Kleine, Tillmann; Bolm, Carsten
<x xml:space="preserve">Abstract</x> Back to basics: A transition‐metal‐free method developed for the synthesis of indazoles involves an inexpensive catalytic system composed of a diamine and K2CO3. Various (Z)‐2‐bromoacetophenone tosylhydrazones were converted into indazoles at room temperature in excellent yields (see example; Ts=p‐toluenesulfonyl). The yield was improved by photoisomerization with UV light when E/Z isomeric mixtures of the starting material were used.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>